Causas de exodoncia en dentición permanente. centro de salud nitiluisa - Bryan Alexander, Silva Calles (2022)
ABSTRACT The present work's research objective was to evaluate the causes of exodontia in the permanent dentition at the Nitiluisa Health Center through a descriptive, cross-sectional, observational, and retrospective study. The sample consisted of 131 medical records obtained through a non-probabilistic convenience sampling of patients who received care from January 2019 - to January 2021, based on inclusion and exclusion criteria. The technique used was an observation, and the instrument was clinical history number 033. The information collected from the medical records was arranged in a checklist, and the SPSS program was used for the analysis of the results. The present investigation concluded that the causes for which extractions were performed were: periodontal disease 45.0%, root retained tooth 25.0%, dentin caries 16.3%, pulpitis 6.9%, pulp necrosis 3.8%, cement caries 2.5% and gingivitis 0.6%. The extracted dental pieces in order from highest to lowest percentage are dental piece 1.8 with 10.6%, piece number 1.5 and 4.6 with 7.5%, and piece 3.6 with 6.9 % in third place. In addition, the age group where the highest number of extractions were recorded was from 56 to 75 years with 54 extractions. Finally, it was shown that the female sex had a higher prevalence of extractions with 119 extractions. Keywords: Dental extraction, permanent teeth, causes of extraction.